Morphology and biological notes of Macrosiagon octomaculata (Gerstaecker) triungulinid and a summary of the knowledge on immature stages of the genus (Ripiphoridae) - Ulysséa, Mônica Antunes; Albertoni, Fabiano Fabian (Papéis Avulsos de Zoologia, 2020)
Species of Macrosiagon Hentz are known to be wasp and bee parasitoids. Here, we present information on Macrosiagon octomaculata (Gerstaecker, 1855), including eggs and triungulinids, found on Paepalanthus polyanthus (Bong.) Sano (Eriocaulaceae) blooming in restinga habitat on Santa Catarina Island, South Brazil. This is the first record of an Eriocaulaceae species playing an important role in the Macrosiagon bionomics and the first accurate record of Ripiphoridae for southern Brazil, Santa Catarina state. In the study area, P. polyanthus attracted an inordinate number of insect species and one Thynnidae wasp was captured with a triungulinid on its wing. Eggs and triungulinids were also found on one plant of P. polyanthus and associated with M. octomaculata. We provide descriptions of the female reproductive organs as well as the morphology of the triungulinid of M. octomaculata. A detailed examination of the triungulinid revealed novelties that complement information from previous publications regarding the Ripiphoridae. We also compare triungulinids of M. octomaculata with those of other species, and provide a table summarizing comparative characters. Finally, we provide a table with current information on the recorded host species and immatures of Macrosiagon.